Pengaruh Digital Marketing terhadap Minat Beli pada 3 Cafe di Kabupaten Jember - Suharto, Fahriza Nurseha; Sanosra, Abadi; Herlambang, Toni (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to assess the impact of continued promotions on purchasing interest at three bistros operating in Jember, namely Rangkum Espresso, At maison, and Mr. Rokar Bistro. This exploration strategy includes investigating information from advanced promotional connections, for example, use of virtual entertainment, online missions, and customer reactions. Measurable test results show that computerized promotions have an impact on purchasing interest in the three bistros, with an importance level of 0.001. Overall, computerized promotions play a big role in shaping buyers' buying interest in these bistros. This exploration adds additional understanding of how the use of computerized media can strengthen advertising techniques and influence purchasing choices in the local bistro industry. The functional consequence of this discovery is that restaurateurs and exhibition specialists can most likely use computerized stages to increase customer purchasing interest and create areas of strength for attendance. Keywords: Buying Interest, Cafe, Digital Marketing, Social Media